Estimation of affective pictures in different phases of menstrual cycle - Mačiukaitė, Laura; Grikšienė, Ramunė; Rukšėnas, Osvaldas (Psichologija, 2010)
Despite extensive investigation and increasing interest in gender differences of cognitive abilities and emotional processing, more questions than answers still remain. There are accumulating data that sex steroid hormones have a strong effect on the functioning of the central nervous system. However, data concerning the effects of these hormones on emotional processing in both genders and during different phases of women’s menstrual cycle are scarce and contradictory. The aim of our study was to investigate how gender and the phase of menstrual cycle influence the evaluation of affective pictures with different attractiveness. Thirty university students (12 men and 18 women), mean age 23.1 ± 2.4 years, participated in this study. Thirty-six images were selected from the International Affective Picture System (IAPS) and grouped into four sets of nine photographs each: three attractive, three neutral, three antipathetic. All subjects participated in four experimental sessions. Images were selected to represent all affective levels (from the least pleasant and arousing to the most pleasant and arousing) during each experimental session. Women were investigated during follicular, ovulatory, luteal and late luteal phases of menstrual cycle confirmed by salivary 17β-estradiol and progesterone assessment. Intervals between men’s experimental sessions corresponded to women’s inter-session intervals determined by phases. The task for subjects was to rate the pictures in valence and arousal dimensions using the Self-Assessment Manikin (SAM) instrument.The study revealed that women estimated affective pictures with a higher valence (t = 2.72, p < 0.01) and a lower arousal (t = –5.70, p < 0.001) than men. The rating of affective images by men was stabile and independent of experimental day. Women rated pictures depending on the phase of menstrual cycle. Attractive pictures were rated as the most pleasant and arousing (statistically significant differences as compared to other phases and men) during the ovulatory (high 17β-estradiol) phase. The rating of neutral pictures did not depend on the phase of the menstrual cycle (except follicular). The rating of antipathetic pictures was less dependent on the phase of menstrual cycle, and in all cases (except luteal, high progesterone phase) these pictures were rated as less pleasant (t = –8.22, p < 0.01) and more arousing (t = 3.85, p < 0.01) as compared to estimates done by men.
Keywords: emotions; sex steroids; menstrual cycle; IAPS